The effects of leg kick on swimming speed and arm-stroke efficiency in the front crawl - Peterson Silveira, R.; de Souza Castro, F. A.; Figueiredo, P.; Vilas-Boas, J. P.; Zamparo, P. (International Journal of Sports Physiology and Performance, 2017)
Purpose: To analyze the effects of swimming pace on the relative contribution of leg kick to swimming speed and to compare arm-stroke efficiency (nyF) assessed when swimming with the arms only (SAO) and while swimming front crawl (FCS) using individual and fixed adjustments to arm-stroke and leg-kick contribution to forward speed.